Full description of Cordulagomphus primaerensis from Santana Formation (Lower Cretaceous of Brazil) (Odonata: Aeshnoptera: Proterogomphidae) - Petrulevicius, Julian Fernando (2012)
Thanks to the discovery of a new specimen, we discuss and confirm the differences proposed by Petrulevičius and Martins-Neto, 2007 (in Bechly, 2007) between Cordulagomphus (Procordulagomphus) primaerensis Petrulevičius and Martins-Neto, 2007 and its close relative Cordulagomphus (Procordulagomphus) michaeli Bechly, 2007.